2018
DOI: 10.4138/atlgeol.2018.012
|View full text |Cite
|
Sign up to set email alerts
|

SHRIMP U–Pb zircon evidence for age, provenance, and tectonic history of early Paleozoic Ganderian rocks, east-central Maine, USA

Abstract: SHRIMP U–Pb zircon ages from Ganderia in eastern Maine clarify the ages and provenance of basement units in the Miramichi and St. Croix terranes and of cover rocks in the Fredericton trough and Central Maine/Aroostook-Matapedia basin (CMAM). These new data constrain timing of orogenic events and help understand the origin of the cover rock depocenters.Detrital zircon data generally confirm suggested ages of the formations sampled. Zircon grains with ages of ca. 430 Ma in both depocenters, only slightly older t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…8). Such peaks are characteristic of sedimentary rocks from Gondwanaderived terranes and reflect the widespread pan-African igneous activity related to the assembly of the Gondwanan continent (e.g., Satkoski et al 2010;Pollock et al 2009Pollock et al , 2015Dokken et al 2018;Ludman et al 2018). It is difficult to assess the significance of the variations in the position of the Ediacaran peak or of the spread in Ediacaran ages in terms of specific provenance areas in Gondwana because even samples from a single belt or stratigraphic unit can display significant differences, as has been documented in the Ganderian parts of New Brunswick, Nova Scotia, and Newfoundland (e.g., Fyffe et al 2009;Satkoski et al 2010;Barr et al 2012;van Rooyen et al 2019).…”
Section: Provenance Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…8). Such peaks are characteristic of sedimentary rocks from Gondwanaderived terranes and reflect the widespread pan-African igneous activity related to the assembly of the Gondwanan continent (e.g., Satkoski et al 2010;Pollock et al 2009Pollock et al , 2015Dokken et al 2018;Ludman et al 2018). It is difficult to assess the significance of the variations in the position of the Ediacaran peak or of the spread in Ediacaran ages in terms of specific provenance areas in Gondwana because even samples from a single belt or stratigraphic unit can display significant differences, as has been documented in the Ganderian parts of New Brunswick, Nova Scotia, and Newfoundland (e.g., Fyffe et al 2009;Satkoski et al 2010;Barr et al 2012;van Rooyen et al 2019).…”
Section: Provenance Implicationsmentioning
confidence: 99%
“…1a), it provides a comparison dataset for areas to the southeast. Ludman et al (2017Ludman et al ( , 2018 suggested that the Fredericton trough represents an independent basin that was not linked to the more southern New England basins, and interpreted the detrital zircon signatures as being derived from dominantly Gondwanan sources. In contrast, Dokken et al (2018) documented more mixed zircon provenance signature with significant Laurentian contributions.…”
Section: Provenance Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, farther NE in Maine, there is a gap between the Liberty-Orrington belt and the Miramichi inlier, where Silurian forearc basin rocks of the Central Maine trough are juxtaposed with Silurian turbidites of the Merrimack-Bucksport-Fredericton (MBF) or "Merribuckfred" (Hussey et al, 2010) belt. The two belts display similar facies and ages, and the boundary between them is difficult to define (Ludman et al, 2018). Most of the sedimentary strata in the Central Maine trough and the northern part of the Fredericton belt are dominated by Laurentian zircon, although some samples show mixed Laurentian and Gondwanan provenance (Dokken et al, 2018;Ludman et al, 2018) The southernmost inlier of pre-Silurian rock in the belt that separates the Merrimack and Central Maine troughs is the Massabesic Gneiss complex of New Hampshire (MSB; Fig.…”
Section: Liberty-orrington Beltmentioning
confidence: 99%
“…The two belts display similar facies and ages, and the boundary between them is difficult to define (Ludman et al, 2018). Most of the sedimentary strata in the Central Maine trough and the northern part of the Fredericton belt are dominated by Laurentian zircon, although some samples show mixed Laurentian and Gondwanan provenance (Dokken et al, 2018;Ludman et al, 2018) The southernmost inlier of pre-Silurian rock in the belt that separates the Merrimack and Central Maine troughs is the Massabesic Gneiss complex of New Hampshire (MSB; Fig. 7).…”
Section: Liberty-orrington Beltmentioning
confidence: 99%